On the preconditioning conjugate gradient method for the solution of 9-point elliptic difference equations - Mazhar, Zeka; Daoud, D.S; Subaşı, Deniz (Elsevier B.V, 1994)
The Preconditioned Conjugate Gradient (PCG) method is implemented to solve the system with 9 diagonal entries generated from a 9-point finite difference approximation of the self-adjoint elliptic partial differential equation using an incomplete matrix decomposition. A simpler matrix decomposition for such a linear system is also proposed with a main advantage that it preserves the symmetry of the original matrix, and is easy to implement. Results of the numerical experiments and comparison with other iterative methods are presented.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Preconditioned conjugate gradient method; iterative method; self-adjoint partial differential equation